EFFECT OF NITROGEN FERTILIZATION ON YIELD AND QUALITY OF WATERMELON, CV. TOP GUN - Dalmazzo Nowaki, Rodrigo Hiyoshi [UNESP]; Cecilio Filho, Arthur Bernardes [UNESP]; De Faria, Rogerio Teixeira [UNESP]; Wamser, Anderson Fernando; Mendonza Cortez, Juan Waldir [UNESP] (Univ Fed Rural Semi-arido-ufersa, 2017)
Nitrogen (N) is the second most important nutrient required by watermelons that can limit their growth and affect fruit quality when deficient. We evaluated the soil (N-nitrate) and foliar N contents and soluble-solid content of the watermelon 'Top Gun' in Brazil at six rates of N fertilization (0, 50, 100, 150, 200 and 250 kg ha(-1)). N-nitrate and foliar N levels increased linearly with rate. Number of total and marketable fruit, weight of total and marketable fruit and total and marketable yields varied quadratically with rate. N rates of 187 and 184 kg ha(-1) produced the highest total and marketable yields, respectively. The rate of N fertilization did not significantly affect total-solid content.
Keywords: Citrullus lanatus; Performance; Fresh weight; Nitrogen fertilization; Soil nitrate